Analysis of central corneal thickness in systemic lupus erythematosus - Saldaña-Garrido, Juan David; Cantó-Cerdán, Mario; Gil-Guillén, Vicente Francisco; Alfaro-Beltrá, María Luisa; Sivera, Francisca (Frontiers in Medicine, 2025)
IntroductionSystemic lupus erythematosus (SLE) is a chronic autoimmune disease with ocular involvement in up to 30% of cases. Due to its type I collagen composition, the cornea is particularly susceptible to thinning due to immune-complex deposition. A reduced central corneal thickness (CCT) is clinically relevant in glaucoma, where a thinner CCT increases glaucoma risk and in refractive surgery planning. Previous studies on CCT in SLE are limited due to methodological heterogeneity, technology use, inclusion criteria, and sample size, resulting in conflicting findings. This study aims to evaluate and compare the mean CCT values between patients with SLE and healthy controls.Materials and methodsThis cross-sectional study assessed mean CCT in 71 participants, 36 patients with SLE and 35 age- and sex-matched healthy controls, recruited from ophthalmology consultations. Participants with other risk factors for corneal thinning were excluded. A pilot study estimated a sample size of 34 participants per group. After confirming concordance using the Kappa index, one randomly selected eye per participant was included. CCT was measured using Zeiss HD Cirrus 5,000 optical coherence tomography. Correlation analysis was conducted using Spearman’s Rho coefficient, while a Loess regression was performed to visualize both linear and non-linear trends. Multivariate linear regression assessed the relationship between CCT, SLE, and other variables.ResultsPatients in the SLE group exhibited significantly thicker CCT than controls (536.44 ± 39.91 μm vs. 517.57 ± 29.62 μm, p = 0.014). Intraocular pressure (IOP) was similar between groups (14.31 ± 3.12 mmHg vs. 14.54 ± 2.36 mmHg, p = 0.898). CCT positively correlated with the length of hydroxychloroquine (HCQ) use (R: 0.357; p = 0.041), showing a trend toward an increase with prolonged usage, peaking approximately 100 months. Multivariate regression confirmed the association between SLE and higher CCT, potentially due to HCQ use.DiscussionWe established an association between CCT and the presence of SLE, with SLE patients exhibiting significantly higher CCT values, potentially due to hydroxychloroquine use. These findings have important implications for IOP assessment, glaucoma risk evaluation, and refractive surgery planning in SLE patients and those undergoing treatment with HCQ. Further prospective studies are warranted to validate these observations and explore the underlying mechanisms.